Prevalance And Acceptability Of Modernization Of Indian Food In Hotels And Restaurants Of Delhi And Ncr (PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: Delhi being the microcosm of innumerable cuisines spread over India, gives  the face to the varying expressions of diverse states and cultures prevailing in it but culinary  globalization has tremendously influenced Indian food by helping us explore the unexplored  facets of ethnicity of our cuisines with an exotic twist comprising the array of magnificent food  in the form of street food, staple diet as well as festival ethnic food. The mobility of people  and ideas has seeded a steady yet dynamic change in the textures, presentation and flavors to  the palette through the nourished approach of culinary modernization. Objective: To analyze  prevalence of modernization of Indian ethnic food in hotels and restaurants of Delhi and NCR.  Methodology: The survey was conducted with the sample size of 150 including the employees  and the guests, Expert chefs, as well as food bloggers and food critics established in different  Hotels and Restaurants situated in Delhi and NCR.Online Questionnaires were circulated in  different hotels and restaurants, to the employees as well as to the guests. Results: The study  was able to gauge and assess the widespread prevalence of modernized Indian food and the  variegated responses of divergent clientele andthe level of acceptability and non-acceptability  of the concept/s of modernization of Indian (ethnic food) amongst the guests and employees  in the Hotels and Restaurants of Delhi and NCR. Majority of the respondents (61.5%) were  aware of the concepts of modernization of Indian Food and gave prominent examples as well.  majority of the respondents (73.1%) were aware about the fusion concepts of Indian food and  could make the distinction between the two i.e. Modernization and fusion of Indian Cuisine  with relevant examples. Conclusion: Modernization of Indian food is a new concept in Indian  Hospitality Industry which is preserving the essence of traditional Indian food.
Keywords: Modernization; Indian food; ethnicity; Hotels